Tinea Capitis In Adolescent: A Case Report - Debora Semeia Takaliuang (Green Publisher Indonesia, 2022)
Background: Tinea capitis is a dermatophyte infection of the scalp, eyebrows, and eyelashes with a propensity for attacking hair shafts and follicles. The treatment remains the same between child, adolescent and adult. Purpose: To understand the clinical manifestation and management of tinea capitis. Case management: A ninety-year-old girl, came to Dermatovenereology Outpatient Clinic Salak Hospital because of baldness on her head since 2 weeks before admission. Dermatological examination demonstrated alopecia with an elongated diameter from parietal dextra to sinistra along 40 cm broken off at the level of the scalp leave behind grouped black dots within patches of polygonal-shaped alopecia with finger-like margins. Wood’s lamp examination not revealed bright green fluorescence. Potassium hydroxide 20% examination was found spores outside and inside the hair shafts. Patient was diagnosed with tinea capitis and was treated with oral griseofulvin 500 mg every 12 hours, cetirizine 10 mg every 24 hours, and ketoconazole 2% shampoo 3 times weekly. At 2 and 8 weeks of follow up, the lesion of her scalp was improved, hair has started to grow, the itchy was gone. Conclusions: Although most commonly seen in prepubescent children, tinea capitis can occur in adults. In adults, women are infected more frequently than men. Auxiliary examination for the diagnosis of tinea capitis can be done in various ways, Woods lamp, potassium hydroxide 20% examination, fungal culture is then performed to determine the species causing the infection. Therapeutic use of griseofulvin is still the main choice.